Mitral Valve Endocarditis-Related Stroke: A Case Report and Literature Review - Darius Adomavicius; Mark Bock MD; Christian-Friedrich Vahl MD; Ekkehard Siegel MD (SAGE Publishing, 2018)
Background. Aerococcus urinae is a rare causative pathogen of infective endocarditis that results in a high risk of embolic events. The mortality rate for A urinae endocarditis is high. Old age and underlying urologic conditions are the best-known risk factors for infection. Case Description. We report the clinical course of the disease in a 49-year-old man who presented symptoms of a urinary tract infection. A few days later, transthoracic echocardiography showed a conspicuous mitral valve with myxomatous alterations. Following the detection of a cerebral embolism with associated stroke symptoms, as well as at the beginning of cardiac failure, the emergency indication for the surgical treatment of mitral valve endocarditis was given. On the second day following the operation, circulatory collapse rapidly developed. Following an unsuccessful attempt at cardiopulmonary resuscitation, the patient died. Review of the Literature. From 1991 to 2017, 29 cases of A urinae -induced endocarditis have been described in PubMed and Medline. One or 2 new cases are published annually. We review all reported cases of A urinae endocarditis, with an emphasis on the predisposing factors, course, and outcomes of the disease. Conclusion. A urinae endocarditis is a rare disease primarily affecting elderly men with urinary tract pathologies and comorbidities. The course of the disease is severe, and the outcome is often fatal. A 16S rDNA polymerase chain reaction investigation of bacterial genome provides proof of the presence of A urinae . Because of the high risk of embolism, rapid treatment should focus on the diseased heart valve. Based on existing data and the experience gained from handling cases, treatment with β-lactam and aminoglycosides is recommended. It is also recommended that operative therapy take place as soon as possible.